THE ROLE OF URIC ACID AND ALANINE AMINO TRANSFERASE IN TYPE 2 DIABETIC MELLITUS - SOMI SETTY. HIMA SAGARIKA; N. MALLIKARJUNA RAO; M.PRASAD NAIDU (International Journal of Pharma and Bio Sciences, 2014)
Type 2 diabetes mellitus is an independent risk factor for cardiovascular disease and the risk for cardiovascular disease is increased three to four fold in non insulin dependent diabetes mellitus as compared to non diabetic population. Lowering levels of uric acid may slow progression of renal disease, especially in patients with hyperuricemia. Alanine Amino Transferase to predict the development of type 2 diabetes independent of BMI and alcohol intake. numerical variable will be summarized as the mean, median and standard deviations for all subjects and student‘t’ test significance of study parameters Altered uric acid levels observed in the type 2 diabetes subjects may be due to deterioration in glucose metabolism associated with hyper insulinemia, metabolic syndrome and its impact on the renal excretion of uric acid. Increasing evidence suggests that Levels of ALT and Uric acid were found to be altered in type 2 diabetic subjects.